2002
DOI: 10.3112/erdkunde.2002.04.03
|View full text |Cite
|
Sign up to set email alerts
|

Landwirtschaft und klimatische Trends im zentralen Yarlong Tsangpo-Tal, Tibet

Abstract: Agriculture and climatic trends in the central Yarlong Tsangpo valley, Tibet The Yarlong Tsangpo valley in southern Tibet is the centre of Tibetan farming. About 75% of the area is cultivated with local barley cultivars with some additional spring and winter wheat. With the exception of the Xigaze basin, cultivation is limited by seasonal flooding to higher ground on terraces, debris fans and small upslope areas in the valley. Generally favourable thermal and solar conditions in the subtropical high-altitude v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…analysed data of the station Amdo, and recorded multi-year oscillations in precipitation from 1965 to the mid1990s, followed by a trend to increasing precipitation since 1995. The July precipitation even slightly decreased until the mid 1990s (Thomas and Chen, 2002). Annual precipitation in the last decade was 50.6 mm (about 12%) above the average annual mean during the period 1965-1994.…”
Section: Climatic Considerationsmentioning
confidence: 93%
See 1 more Smart Citation
“…analysed data of the station Amdo, and recorded multi-year oscillations in precipitation from 1965 to the mid1990s, followed by a trend to increasing precipitation since 1995. The July precipitation even slightly decreased until the mid 1990s (Thomas and Chen, 2002). Annual precipitation in the last decade was 50.6 mm (about 12%) above the average annual mean during the period 1965-1994.…”
Section: Climatic Considerationsmentioning
confidence: 93%
“…The same tendency was observed by Shi et al (2006), Kang et al (2007b), and Chen et al (2009) for the stations adjacent to our study region. Pan evaporation showed stable or slightly increasing values until the mid 1990s (Thomas and Chen, 2002) and a decrease thereafter (Liu et al, 2010).…”
Section: Climatic Considerationsmentioning
confidence: 96%
“…The TP was identified as the only large contiguous region in China were potential yields were declining. This is underlined by a regional study where decreasing precipitation and increasing PET rates in summer have been shown to affect the largest crop growing region in central Tibet (Thomas and Chen, 2002) by lowering potential yields by up to 12% during the last 50 years. Despite generally decreasing PET rates water balance studies therefore point to generally decreased water availability for field crops during the last decades.…”
Section: Impacts Of Pet Trendsmentioning
confidence: 95%
“…From 1951 to 1993 annual PET rates in the eastern part of the TP showed both increasing and decreasing trends of more than 20 mm/decade (Thomas, 2000a). In the Yarlong Tsangpo valley (Central Tibet) July PET rates have decreased moderately by 7.5 mm/decade between 1954-1993(Thomas and Chen, 2002. For the upper reaches of the Yellow River Li et al (2000) reported an annual increase of 3.3 mm during the summer months (May to October) from 1981 to 1998.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation